Private Retirement Scheme in Malaysia: Legal Analysis - Ali, Azlin Namili Mohd; Yeon, Asmah Laili; Hussain, Mohammad Azam (International Journal of Economics and Financial Issues, 2016)
The Government recognizes the significance of savings to guarantee sufficient savings after retirement. In this regard, the Malaysian Government established the Private Retirement Scheme (PRS) in 2012 as a complementary scheme to the existing pension schemes. PRS seeks to provide alternatives for employed or self-employed Malaysian citizens, to enhance a well-structured and regulated scheme. By using a legal research approach, this study seeks to analyse the existing legislations governing PRS in Malaysia. The study found that the PRS is mainly regulated by Capital Markets and Services Act 2007 and other legislations. There are several legal challenges that can be observed in PRS system. Among them are PRS Guidelines 2012 only provide a minimum standard in relation to the governance policy of PRS providers and CMSA is silent in the matters regarding PRS scheme based on Shariah principles to be offered by the providers. Keywords: Private Retirement Scheme, Legal Framework, Investment Law, Islamic Private Retirement Scheme JEL Classifications: G21, G23, K3